2009
DOI: 10.1080/15548730902855088
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor Preferences for the Design and Delivery of Training

Abstract: Although the consensus is that training for child protective services (CPS) supervisors is essential, there is an apparent gap in the literature about how the training should be delivered. Using interviews, focus groups, and a statewide survey, supervisors in Arizona identified how, when, and where they wanted training delivered and their reasons why. The preferred methods balance training within the responsibilities and time demands of the supervisor role

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
0
1
Order By: Relevance
“…The inability to undertake the follow-up interviews meant that the reasons for this could not be explored. This finding contrasts with the results from other studies which have found that participants valued peer interaction in online allied health supervisor training programs (Dalton et al 2007, MacEachron et al 2009. Jippes et al (2013) suggest that social networks may improve the adoption of educational innovations by clinical supervisors.…”
Section: Discussioncontrasting
confidence: 95%
“…The inability to undertake the follow-up interviews meant that the reasons for this could not be explored. This finding contrasts with the results from other studies which have found that participants valued peer interaction in online allied health supervisor training programs (Dalton et al 2007, MacEachron et al 2009. Jippes et al (2013) suggest that social networks may improve the adoption of educational innovations by clinical supervisors.…”
Section: Discussioncontrasting
confidence: 95%